Adaptive power load restoration considering flexible control of air conditioners for resilience enhancement. (June 2023) - Fan, Rui; Sun, Runjia; Liu, Yutian; Gryazina, Elena; Terzija, Vladimir
Highlights: An adaptive load restoration strategy fitting to power grid operating conditions and outage scenarios. Step-by-step load restoration taking full use of flexible control of air conditioners and multiple power sources. An aggregated power estimation model for cold load pickup of air conditioners. A flexible load pickup amount reduction method considering the impact degree of air conditioners control on the customer. Abstract: Frequent extreme hot weather brings a surge of air conditioner load and further increases the probability of outages. Fitting to different power grid operating conditions and outage scenarios, an adaptive load restoration strategy is proposed, which can take full use of flexible control of air conditioners and reliable power sources from the power grid and distributed generations or microgrids. Considering the influence of outage duration and environmental temperature, an air conditioner aggregated power estimation model is established to evaluate the cold load pickup amount. Based on the allowable maximum load pickup amount, a load pickup amount reduction method by flexible control of air conditioners considering the impact degree on the customer is proposed to guarantee secure load pickup operation. Simulation results of the IEEE 14-bus system and a practical power grid demonstrate that the proposed method can restore the power supply of customers rapidly and securely to enhance power grid resilience under extreme hot weather.